Effect of menthol in experimentally induced ulcers: Pathways of gastroprotection - Rozza, A. L. [UNESP]; Hiruma-Lima, C. A. [UNESP]; Takahira, Regina Kiomi [UNESP]; Padovani, C. R. [UNESP]; Pellizzon, C. H. [UNESP] (Elsevier B.V., 2013)
Based on ethnopharmacological indications that Mentha species may be used in the treatment of gastrointestinal diseases, this study aimed to characterize the gastroprotective mechanisms of menthol (ME), the major compound of the essential oil from species of the genus Mentha. The gastroprotective action of ME was analyzed in gastric ulcers that were induced by ethanol or indomethacin in Wistar male rats. The mechanisms responsible for the gastroprotective effect were assessed by analyzing the amount of mucus secreted, involvement of non-protein sulfhydryl (NP-SH) compounds, involvement of calcium ion channels and NO/cGMP/K-ATP(+) pathway, gastric antisecretory activity and the prostaglandin E-2 (PGE(2)) production. The anti-diarrheal activity and acute toxicity of ME were also evaluated. Oral treatment with ME (50 mg/kg) offered 88.62% and 72.62% of gastroprotection against ethanol and indomethacin, respectively. There was an increased amount of mucus and PGE(2) production. The gastroprotective activity of ME involved NP-SH compounds and the stimulation of K-ATP(+) channels, but not the activation of calcium ion channels or the production of NO. The oral administration of ME induced an antisecretory effect as it decreased the H+ concentration in gastric juice. ME displayed anti-diarrheal and antiperistaltic activity. There were no signs of toxicity in the biochemical analyses performed in the rats' serum. These results demonstrated that ME provides gastroprotective and anti-diarrheal activities with no toxicity in rats. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Menthol; Gastroprotection; Gastric ulcer; Diarrhea; Acute toxicity